Perkembangan Teknologi Informasi Dan Komunikasi Dalam Pembelajaran Pendidikan Agama Islam - Oktavianti Nendra Utami; Khoirunnisa Endah Setiawati; Eka Salma Dina; Mau’idi Hafida; Unik Hanifah Salsabila (Jurnal Pendidikan Islam, 2023)
The development of technology today has shown its influence on human life. Not only in individuals but society as a whole also feels changes, and it can be said that the progress of science and technology cannot be let go. Modern technology today makes many people like it and then imitate it in terms of lifestyle without any selection first with all the negative impacts that are in it for the future. The purpose of this writing is to find out the development of technology in Islamic religious education. The method used in this article is a literature study by looking for references to books and journal articles related to this topic of discussion. As social beings, humans also need communication with each other to connect, and it is from there that humans begin to look for and create tools that can be used to communicate.